Upward spirals of positive emotions and religious behaviors. (August 2021) - Van Cappellen, Patty; Edwards, Megan E; Fredrickson, Barbara L
Highlights: Certain positive emotions arise from and create religious and spiritual experiences. Worship, prayer, and meditation generate positive emotions such as awe or gratitude. Biological, social, and psychological resources predict greater positive emotions. These positive emotions have consequences for well-being and behavior maintenance. Findings are integrated in the Upward Spiral Theory of Sustained Religious Practice. Abstract : Positive emotions feel good and build psychological, social, and biological resources (Broaden-and-Build Theory, Fredrickson, 1998, 2013). People who identify as religious or spiritual value them and report feeling them frequently. They are also prevalent in religious and spiritual practices, such as prayer, meditation, and collective worship. We review the literature on the reciprocal relationship between positive emotions and religion/spirituality and identify individual differences predicting greater positive emotions derived from engaging in religious practices. We suggest that beyond building religious/spiritual people's well-being, positive emotions play a role in sustaining otherwise costly religious behaviors. We integrate our review in the proposed Upward Spiral Theory of Sustained Religious Practice.